DELLA proteins modulate Arabidopsis defences induced in response to caterpillar herbivory - Lan, Zhiyi; Krosse, Sebastian; Achard, Patrick; van Dam, Nicole M; Bede, Jacqueline C (Journal of experimental botany, 2014)
Upon insect herbivory, many plant species change the direction of metabolic flux from growth into defence. Two key pathways modulating these processes are the gibberellin (GA)/DELLA pathway and the jasmonate pathway. In this study, the effect of caterpillar herbivory on plant-induced responses was compared between wild-type Arabidopsis thaliana (L.) Heynh. and quad-della mutants that have constitutively elevated GA responses. The labial saliva (LS) of caterpillars of the beet armyworm, Spodoptera exigua, is known to influence induced plant defence responses. To determine the role of this herbivore cue in determining metabolic shifts, plants were subject to herbivory by caterpillars with intact or impaired LS secretions. In both wild-type and quad-della plants, a jasmonate burst is an early response to caterpillar herbivory. Negative growth regulator DELLA proteins are required for the LS-mediated suppression of hormone levels. Jasmonate-dependent marker genes are induced in response to herbivory independently of LS, with the exception of AtPDF1.2 that showed LS-dependent expression in the quad-della mutant. Early expression of the salicylic acid (SA)-marker gene, AtPR1, was not affected by herbivory which also reflected SA hormone levels; however, this gene showed LS-dependent expression in the quad-della mutant. DELLA proteins may positively regulate glucosinolate levels and suppress laccase-like multicopper oxidase activity in response to herbivory. The present results show a link between DELLA proteins and early, induced plant defences in response to insect herbivory; in particular, these proteins are necessary for caterpillar LS-associated attenuation of defence hormones.